Memoirs of a cold warrior : the struggle for nuclear parity - Carpenter, Lee, 1925- (Algora Pub., 2009)
As Russia re-asserts itself on the global stage, and now the Peoples Republic of China, too, a look back at the hard, cold facts of the Cold War may improve Americans? understanding of our relative strengths and weaknesses and the continuing vulnerability of our primacy in the world. A defense analyst who served on the frontlines of the struggle for military parity, the author was party to the steps taken by US military, technical and industrial groups to assess, counter, and of course to seek to outperform Moscow throughout the Cold War, until the "collapse" of the Soviet Union